Analisis Hubungan Persepsi Mutu Pelayanan Antenatal Terhadap Kepuasan Ibu Hamil Di Puskesmas Bangetayu Kota Semarang Tahun 2014 - Mumpuni Sari Kusumastuti; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
>One of efforts for reducing maternal mortality rate (AKI) was done by improving the service quality. The service quality of ANC constitutes demands of society, thus within its capacity in health centers, midwives are demanded to be able to provide the better service quality of ANC in order to provide maternal satisfaction. From several health centers in Semarang City, the maternal mortality rate is high in Bangetayu health centers. The high mortality rate was due lack of optimal service quality, thus affecting the level of maternal satisfaction. This research aimed to analyze the relationship of antenatal service quality – which includes perception of reliability, responsiveness, assurance, empathy and physical proofs with thesatisfaction of pregnant women in Bangetayu Semarang health center. Population is pregnant women who perform checks in Bangetayu Semarang health by 2.330, with a sample of 96 respondents. Data analysis was performed using univariate and bivariate analysis chi-square test. The test results showed that the perception of reliability has a relationship with the satisfaction of pregnant women (p-value = 0.000). Perception of responsiveness has a relationship with maternal satisfaction (p-value = 0.000). Perceptions of warrant has a relationship with the satisfaction of pregnant women (p-value = 0.000). Perception of empathy has a relationship with the satisfaction of pregnant women (p-value = 0.000). Perceptions of the physical proof has a significant relationship with the satisfaction of pregnant women (p-value = 0.000). By the proven results of this research, it is necessary to improve the quality of antenatal service speed, so that pregnant women need not to wait too long, as well as midwives empathy in providing explanation of the benefits of the drug to the pregnant women